Prevalence of sarcopenic dysphagia in the geriatric population - Portinha, Susana Maria Aparício Gaspar (2020)
Introduction: Oropharyngeal Dysphagia (OD) and sarcopenia have been recognized as geriatric syndromes and have shown a higher prevalence in institutionalized elderly, being associated with increased socioeconomic burdens. Prevalence of Sarcopenic Dysphagia (SOD) seems to increase with the average age of population. Objectives: To investigate the presence of sarcopenia and risk of OD in a geriatric population and to analyse the relationship between the factors associated with SOD. Methodology: Cross-sectional study conducted in two nursing homes in Tomar. The OD was screened using The Gugging Swallowing Screen (GUSS). Sarcopenia was assessed according to the criteria defined by the European Working Group on Sarcopenia in Older People. The nutritional status was screened using the Mini Nutritional Assessment - Short Form (MNA-SF), and independence in daily living activities (ADL) was assessed using the Barthel Index (BI). The sample was divided into 4 groups, based on the diagnosis: G1 - Without pathology; G2 - Only being at risk of having OD; G3 - Only with sarcopenia; G4 - With probable SOD. Comparisons were made between the different groups, univariate analyses were performed to find the predictors for each group, and finally, a correlational study between the different scales used. Results: We studied 36 elderly people (23 women; 13 men; age 88.0 ± 5.6), 55.6% were at risk for DO, 52.8% had sarcopenia and 36.1% were probable SOD. Literacy was lower (p<.05) in women. The prevalence of malnutrition based on MNA-SF was 19.4%. The most elderly were independent in ADL (91.7%). The results of the univariate analysis of individuals in different groups showed that the SARC-F questionnaire was a significant predictor (OR=9.0; CI95%=1,285-63,025) for the risk of having SOD. Conclusions: The prevalence of OD risk and sarcopenia has increased with age and with the risk of malnutrition or malnourishment. We have observed that female gender, low educational level and score ≥4 on the SARC-F screening test are associated with higher odds of being at risk for OD, sarcopenia, and even probable SOD. We found that the use of badly adjusted artificial teeth increases odds for sarcopenia by 50%, and that this condition was a significant predictor (p<.05) of risk for OD. Based on the results, we suggested including a Speech and Language Therapist in the multidisciplinary geriatric teams in order to improve the prevention of OD, sarcopenia and SOD, avoiding its consequences.